2012
DOI: 10.3174/ajnr.a3012
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Accuracy of Dynamic Contrast-Enhanced MR Imaging Using a Phase-Derived Vascular Input Function in the Preoperative Grading of Gliomas

Abstract: BACKGROUND AND PURPOSE:The accuracy of tumor plasma volume and K trans estimates obtained with DCE MR imaging may have inaccuracies introduced by a poor estimation of the VIF. In this study, we evaluated the diagnostic accuracy of a novel technique by using a phase-derived VIF and "bookend" T1 measurements in the preoperative grading of patients with suspected gliomas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
24
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 16 publications
4
24
0
Order By: Relevance
“…The diagnostic accuracies of DCE-derived parameters in this study were in the range of previously published data from 2 studies, 1 by using a hot spot method and 1 by using histogram analysis. 13,18 The accuracy of DSC-derived rCBV in this study was also similar to that in previous studies using hot spot analysis. 1,19 Using the bookend T1 mapping and phase-derived VIF, we also found that DCE-derived Vp and K trans were lower for grade II than for grade III astrocytomas.…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations
“…The diagnostic accuracies of DCE-derived parameters in this study were in the range of previously published data from 2 studies, 1 by using a hot spot method and 1 by using histogram analysis. 13,18 The accuracy of DSC-derived rCBV in this study was also similar to that in previous studies using hot spot analysis. 1,19 Using the bookend T1 mapping and phase-derived VIF, we also found that DCE-derived Vp and K trans were lower for grade II than for grade III astrocytomas.…”
Section: Discussionsupporting
confidence: 75%
“…This limitation can be overcome by using phase images to derive the VIF. [9][10][11][12][13] Phase measurements are less biased by intensity changes from inflow and relaxation effects. Magnitude-derived vascular input functions can underestimate the contrast concentration measurement during the first pass (if Ͼ5 mmol/L), especially when a high-relaxivity agent is used.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Advanced physiologic 1 H-MR imaging techniques such as perfusion-weighted imaging, diffusion-weighted imaging, and spectroscopy ( 1 H-MR spectroscopy) provide relevant information for tumor characterization as well. For example, tumor grade is associated with relative cerebral blood volume [32][33][34] ; volume transfer coefficient [35][36][37][38] ; apparent diffusion coefficient 39,40 ; and cerebral metabolite ratios, for example, the choline to N-acetylaspartate 33 and the choline to creatine ratios. 33,41 Also, relative cerebral blood volume, 34,[42][43][44][45][46][47][48] volume transfer coefficient, 35,49 apparent diffusion coefficient, 50-52 and metabolite ratios, for example, the choline to Nacetylaspartate ratio, 53 aid prediction of PFS.…”
Section: Discussionmentioning
confidence: 99%